Design of fibre array muscle for soft finger with variable stiffness based on nylon and shape memory alloy. (2nd May 2020) - Yin, Haibin; Tian, Lei; Yang, Guilin
ABSTRACT: Artificial muscles are increasingly utilized as mechanical actuators owing to their good adaptability and high power-to-mass ratio. The implementation of fibrous artificial muscles in soft robots is of particular interest because of their good adaptability, reduced sectional area, and compact structure. To apply fibrous muscles, their actuation properties should include large deformations and high load capacities. However, single fibres usually do not possess both properties. Thus, fibre array muscles that can balance the large deformations and high loads have become a key objective in the actuator design. Based on nylon and a shape memory alloy (SMA), a composite fibre was developed to design fibre array muscle for the soft finger with variable stiffness in this study. The driving force of the fibre array muscle was predicted based on the requirements regarding the grasping force of the soft finger. Finally, the ply number of the fibre array muscle was determined through a series of experiments. GRAPHICAL ABSTRACT: